REPRESENTATION OF WOMEN IN MEDIA SITES ONLINE - Novi Andayani Praptiningsih (STKIP Singkawang, 2017)
Dream.co.id site content articles and images predominantly women, where there are 429 articles in the category of housewives and career. The site is the site of the Muslim lifestyle who ranks 10th in Indonesia. Recorded census at the end of 2016 as much as 49.83%, or about 118.3 million people is the female population. The Central Bureau of Statistics recorded at 60.67% of Indonesian women married, had a position as a housewife and also work. These facts explain that women have multiple roles. The research objective was to determine the representation of women in the Online site. The method used is the analysis of the contents of the article content Dream.co.id by framing the article connecting concept and as a mark of meaning production. There are three theories that explain the representation. First, gender representation and gender is shaped by culture. Gender representation in media produces negative stereotypes of women, where women are always positioned in the domestic sphere. Second, representation and realism that is the real picture that is displayed media. Content received an audience is a form of real world. Third, changes in the representation of where the text that appears to have an important meaning message (Branston & Stafford, 2003). The findings show that 67% of women described as having two roles. Women have a function take on the role of tradition and role transitions. Women have a great responsibility in the domestic sphere and the public. A role can be an option for women themselves, but also as the demands on women. Both of these roles as a breakthrough of postfeminis, but is still undergoing structural traditionalists. On the site's content was found to be 71.7% of women get the stereotypical 'housewife'. The 28 articles category housewives and career are 57.1% on a female stereotypes about the 'housewives' negative tone in the media portal Dream.co.id, such as : housewives make a loss because it does not work and the purchase of foreign products, father was a non-commissioned officer who just married housewife, housewife better than career, women should be more at home and be a housewife, a wife/mother perform all household tasks such as cooking, washing, embroidery, childcare, care of the home, children, husband, being a housewife into the nature of monthly expenditure, women as domestic servants work caring for children, can work under pressure, a little rest, good at cooking, washing, can take care of their own health, and finally women should be housewives.Conclusion is different roles and weights, two different terms. Private role is to take care of the family. While household problem is not a requirement for women. Sincerity women who want to perform household duties while caring for children and a husband. The system of values, norms, stereotypes and gender ideology has long been seen as one of the factors that influence women's position and relationship with men, or with the environment in the construction of society. The role of women in the public sphere of the economy is getting the salary from his own sweat where the money is not an obligation to use on families. Women who want to help and share their income to domesticate the supposed obligation of men referred to as alms. Alms in financial terms given willingly by the woman/wife to the household as a form of glory and grace of a woman. Each role taken by women has a positive function for themselves, society and beliefs.